The Influence of Marketing Mix, Reputation and Credibility on Student Decisions to Choose Private Universities in the City of Bandung - Lestari, Heni Sri; Miswan, Miswan; Suryanto, Suryanto (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
This study aims to measure and analyze the factors in the service marketing mix and image formation, namely reputation and credibility which can influence consumer selection decisions. More specifically, this research takes the context of educational services, with students as consumers who perceive the Bandung College of Administrative Sciences (STIA) as their preferred private university. This research was conducted using a quantitative method on 110 STIA Bandung students who were determined by the simple random sampling method. Data were obtained from observations, documented studies, distributing questionnaires to respondents, as well as interviews with leaders and staff within the campus environment. The results of this study indicate that the three marketing mix variables, reputation and credibility have a positive and significant effect on the decision to choose a university in Bandung. Thus, tertiary institutions need to apply these three variables as a strategy to attract students to choose a tertiary institution.